2016
DOI: 10.1016/j.jid.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The Aldo-Keto Reductase AKR1B10 Is Up-Regulated in Keloid Epidermis, Implicating Retinoic Acid Pathway Dysregulation in the Pathogenesis of Keloid Disease

Abstract: Keloid disease is a recurrent fibroproliferative cutaneous tumor of unknown pathogenesis for which clinical management remains unsatisfactory. To obtain new insights into hitherto underappreciated aspects of keloid pathobiology, we took a laser capture microdissection-based, whole-genome microarray analysis approach to identify distinct keloid disease-associated gene expression patterns within defined keloid regions. Identification of the aldo-keto reductase enzyme AKR1B10 as highly up-regulated in keloid epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 125 publications
0
23
0
Order By: Relevance
“…Our data also identified a significant upregulation of AKR1B10 (as well as AKR1B1 and AKR1B15 ) in all three sites of the KE. This enzyme has a key role in the metabolism of retinoic acid (RA) and our recent study found the induced overexpression of AKR1B10 in NS keratinocytes resulted in significant downregulation of E-cadherin [23]. Additionally, the treatment of keloid fibroblasts with AKR1B10-overexpressing keratinocyte medium resulted in upregulation of TGF β1, Collagen I and collagen III, supporting a role for pathological epithelial-mesenchymal interactions (EMI) in keloid pathogenesis.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our data also identified a significant upregulation of AKR1B10 (as well as AKR1B1 and AKR1B15 ) in all three sites of the KE. This enzyme has a key role in the metabolism of retinoic acid (RA) and our recent study found the induced overexpression of AKR1B10 in NS keratinocytes resulted in significant downregulation of E-cadherin [23]. Additionally, the treatment of keloid fibroblasts with AKR1B10-overexpressing keratinocyte medium resulted in upregulation of TGF β1, Collagen I and collagen III, supporting a role for pathological epithelial-mesenchymal interactions (EMI) in keloid pathogenesis.…”
Section: Resultsmentioning
confidence: 97%
“…Our recent publication on the upregulation of AKR1B10 in KE, where we hypothesised its ability to catalyse the reduction of carbonyls and xenobiotics may render keloid susceptible to chemotherapeutic resistance and thus explain some of the difficulties associated with management of KD to date [23, 151]. Both ALDH1A1 and the aforementioned upregulation of NOTCH4 in KE are also associated with drug resistance [152, 153].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the response rate was quite uncertain, varying from 50% to 100%. [18,19] The control of recurrence rate was also fluctuating, ranging from less than 10% to over 50%. [20,21] The most common adverse effects included dermal atrophy, telangiectasia and local pain at the injection site.…”
Section: [17]mentioning
confidence: 99%
“…Although keloid is a benign dermal tumor, its management remains an excessively challenging clinical problem. Keloids do not regress with time, and surgical excision alone is associated with high rates of recurrence [1,3]. Keloid disease is a recurrent fibroproliferative cutaneous tumor of unknown pathogenesis for which clinical management remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%